STRATEGI CYBER PUBLIC RELATIONS POLRI DALAM MENUJU CITRA YANG PRESISI ( PREDIKTIF, RESPONSIF, TRANSPARANSI BERKEADILAN - Allika Fadia Haya (2022)
The results of the study indicate that this study aims to discuss how the Cyber Public Relations strategy of the National Police Public Relations Division leads to a precise image and the obstacles faced by Cyber Public Relations towards a precise police image. The method used is descriptive qualitative by using primary data sources and secondary data. Data collection techniques were carried out by in-depth interviews and documentation. The theory used is CMC (Computer Mediated Communication) which is a theory in which interpersonal interactions are carried out through computer technology and are related in the process of forming various medical purposes. The result of the research is that the Cyber Public Relations strategy of the National Police Public Relations Division is viewed from the process of fact finding, planning, communicating and evaluating. The image of the Police that is owned by Citra Polri now with the Cyber Public Relations strategy that has been implemented can be said to be a Presisi. As Cyber Public Relations, he has the task of working in the field of Public Relations assisted by the internet and technology for the success of the Presisi.Constraints experienced by the Multimedia Division of the Police Public Relations. Division in charge of Cyber Public Relations to achieve a precise image on social media include the lack of human resources or members of the Police in the Multimedia field, consisting of 15 personnel. So that it is not optimal in responding to the community in social media YouTube, Facebook, Twitter and Instagram.